Evaluating an evidence-based iSupport for Dementia programme in routine care services: study protocol for a hybrid type II trial - Jing Wang; Shahid Ullah; Ying Yu; Rujun Hu; Lily Dongxia Xiao; Xiaoying Pan; Ada Cheng; Candy Xie; Kam Chiu; Dingxin Xu; Angela Rong Yang Zhang (BMJ Open)
Introduction Disparities in supporting carers of people with dementia exist in carer populations. The WHO developed an evidence-based iSupport for Dementia programme to address the disparities. However, evidence on how to embed the iSupport programme in routine health and aged care services to optimise support for carers remains largely unknown.Methods and analysis This study will apply a hybrid type II effectiveness-implementation trial to evaluate the embedment of two iSupport innovations: ‘usual iSupport’ and ‘tailored iSupport’ in health and aged care services in Australia and China. The RE-AIM framework informed the study design. Three aged care organisations in Australia, two public hospitals and a community health centre in China will participate in the trial by delivering the two iSupport innovations to 158 carers of people with dementia with 79 carers in each intervention group using a randomised controlled trial design. The effectiveness of the two iSupport innovations will be determined by measuring the quality of life and self-efficacy of carers, and the quality of life of people with dementia, unplanned hospital admissions, emergency department presentations and admissions to permanent nursing homes and perceived quality of care of people with dementia at baseline, 3 months and 6 months. The effectiveness of strategies used to embed the iSupport innovations in routine care services will be evaluated using qualitative data collected from focus groups or interviews with carers, staff and management involved in the study and records from the participating organisations.Ethics and dissemination Ethics approval was obtained from Flinders University (project number: 5819), Xi’an Jiaotong University (project number: 2023–1629) and Zunyi Medical University (project number: KLL-2023–245). We will obtain informed written or oral consent from participants in the trial. We will publish the results in peer-reviewed journals to disseminate the study and generate impact on policy and practice changes.Trial registration number ACTRN12623000323628; The Australian New Zealand Clinical Trials Registry (ANZCTR); registered on 27 March 2023.